Light as an expression tool: dialogues about thinking and the sensory use of colors in Nadja Naira's work (A Luz em Cena: Revista de Pedagogias e Poéticas Cenográficas, 2024)
This article presents an excerpt from the master's research entitled Color on stage: a study on sensoriality in scenic creation processes, carried out with the Programa de Pós-graduação em Artes Cênicas, da Universidade Federal de São João del-Rei, as a project linked to the Núcleo de Estudos em Técnicas e Ofícios da Cena, do Grupo de Estudos em História, Política e Cena (NETOC/GPHPC/UFSJ). This is the exposition and analysis of part of the data collected during the investigation, consisting of the selection of excerpts from the interview carried out with the illuminator Nadja Naira, on February 26, 2022, through the zoom videoconferencing platform. In addition to the selected materials, the article aims to make a partial presentation of the results obtained and disseminate the work methodology used during the investigation.
Keywords: Scenic lighting; Color; Sensation